2019
DOI: 10.1080/24759651.2019.1688603
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of photosynthetically synthesized poly(3-hydroxybutyrate) using a randomly mutated strain of Synechocystis sp. PCC 6714

Abstract: Conventional polymers are made from fossil resources and consume fossil energy in their production, yielding CO 2 emissions. Production of large-volume compounds from CO 2 , either from point sources or from the air, could reduce anthropogenic global warming. Poly(3-hydroxybutyrate) (PHB) is a biodegradable and biobased thermoplastic polymer which can be synthesized sustainably using CO 2. PHB exhibits a high crystallinity and shows properties similar to synthetic polyesters and also to polyolefins such as pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In addition, a glass transition temperature similar to the present study was found in a strain of Synechocystis sp. [ 34 ]. Nevertheless, the glass transition temperature of PHB extracted from Lysinibacillus sphaericus was 140 °C, proving that high glass transition temperatures of different types of PHB can be determined in different microorganisms [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a glass transition temperature similar to the present study was found in a strain of Synechocystis sp. [ 34 ]. Nevertheless, the glass transition temperature of PHB extracted from Lysinibacillus sphaericus was 140 °C, proving that high glass transition temperatures of different types of PHB can be determined in different microorganisms [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The physicochemical and morphological characterization of PHB provide a clear understanding of the polymeric properties when compared to polymers of petrochemical origin and they have not been already well-developed in bacteria biopolymers [ 10 ]. Marine cyanobacteria and microalgae have become more sensitive to this low manipulation and offer further research that confirms the large and useful properties of these polymers for later use in medical applications such as drug carrier biomaterials, tissue engineering scaffolds, and others [ 21 , 24 , 34 , 35 , 36 ]. The aim of this article was therefore to study the chemical, physical, morphological, and biological characterization of a novel biotechnological polyhydroxybutyrate by microalgae Stigeoclonium sp.…”
Section: Introductionmentioning
confidence: 99%
“…In previous analyses the average molecular weight of PHB from Synechocystis and Synechocystis sp. PCC 6714 was determined at Mn ~ 130 and 316 kg mol −1 , respectively [ 27 , 37 ]. Compared to these, the PHB derived from PPT1 with an average weight of 503 kg/mol is high-molecular.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical properties of PHBs are similar to the properties of petroleum-based plastics such as polyethylene (PE) and polypropylene (PP) [67]. The PHAs do not need any arable land for the production and can be even produced from CO 2 in a marine environment [75,76].…”
Section: Types Of Biopolymersmentioning
confidence: 99%